Practical Learning and Theory-Practice as Perceived by Student Nurses in Universiti Malaysia Sabah - Hairie Aiery; Nur Izzati M. T.; Ivyta D; Farah Ezora Shafine A. B.,; Sukhbeer K. Darsin Singh,; R. Segaran (2018)
Introduction: The theory-practice gap is arguably the most important issue in nursing today, given that it challenges the concept of research based practice, which is the basis of nursing as a profession. Majority of the student nurses shared their views that some of the practical procedures that they learned during their theory sessions was different from what was practiced in the wards which caused some worries among the student’s that it may affect their performance during their Obstructive Structured Clinical Examination (OSCE). Aim: The aim of this study is to determine the perception of nursing students’ towards the practical learning and strategies to bridge the theory-practice gap. Method: Survey questionnaires pertaining to perception towards the practical learning and strategies to bridge the gap were distributed among 60 UMS students nurses Year 2 and Year 3 to understand their perception on theory-practice gap. Results: As for clinical practice experience, all (100%) students stated that clinical instructor and nursing educators did orientation during the first time in the wards or clinic. Forty students (66.67%) responded “yes” that supervision occurs all the time during the clinical posting. As for practical learning, all students indicated that simulation lab was found in their faculty and nursing block. On strategies, 50 (83%), students agreed that it is helpful if nurse educators spend time in clinical practice to update their skills and re-experiencing the realities of practice. Thirty eight (63%) students agreed that that they need clarification of difficult concepts from staff nurses, clinical instructors and nurse educators. Conclusion and Recommendations: Responses from students have suggested some strategies in bridging the gap between theory and practice such as continuous communication between the education and clinical area.